2021
DOI: 10.1002/sstr.202100033
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Magnetic Microwave Absorption at Low‐Frequency Band by Ferrite Assembled Microspheres with Controlled Components and Morphologies

Abstract: Because of the frequency‐dispersion characteristic, electromagnetic wave energy dissipation depends mainly on the magnetic loss at low frequency (S‐band, 2–4 GHz). Herein, a strong magnetic microsphere is constructed via a simple spray drying and subsequent calcination process. With the reaction temperature increasing, the microparticles are forcibly assembled by different contents of ferrite crystallites and Fe metal (mainly containing Fe2O3, Fe5O12, FeO, and Fe), accompanying morphology evolution. Attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In addition, the ratio of tanδ ε /tanδ μ for CoNi/MnO@C is mostly greater than 1 in the high-frequency range, corresponding to the effective absorption band range of 10-18 GHz (Figure S13d, Supporting Information), which proves that the dielectric loss is dominant. [63,64] It can be observed that the ε′ of CoNi/MnO@C (Figure S14a, Supporting Information) demonstrates conspicuous frequency dissipation behavior at 2-18 GHz, indicating reinforced polarization loss. [65][66][67] Additionally, the ε″ of CoNi/MnO@C (Figure S14b) demonstrates a considerable improvement with respect to MnO@C, Co/MnO@C, and Ni/MnO@C, confirming its strong dielectric loss capability.…”
Section: Defects Interfaces Conductivity and Electromagnetic Attenuat...mentioning
confidence: 99%
“…In addition, the ratio of tanδ ε /tanδ μ for CoNi/MnO@C is mostly greater than 1 in the high-frequency range, corresponding to the effective absorption band range of 10-18 GHz (Figure S13d, Supporting Information), which proves that the dielectric loss is dominant. [63,64] It can be observed that the ε′ of CoNi/MnO@C (Figure S14a, Supporting Information) demonstrates conspicuous frequency dissipation behavior at 2-18 GHz, indicating reinforced polarization loss. [65][66][67] Additionally, the ε″ of CoNi/MnO@C (Figure S14b) demonstrates a considerable improvement with respect to MnO@C, Co/MnO@C, and Ni/MnO@C, confirming its strong dielectric loss capability.…”
Section: Defects Interfaces Conductivity and Electromagnetic Attenuat...mentioning
confidence: 99%
“…The entering electromagnetic waves are scattered and reflected back between the adjacent Ti 3 C 2 T x sheets and SrFe 12 O 19 plates numerous times according to a cycle process until being completely absorbed. [25] Using MWCNTs as a separator, a highly conductive MCSF film with a sinuate lamellate structure and crack-shaped microspores can be used to produce multiple internal reflections to attenuate EM waves. Therefore, a unique combination of the EM wave absorption and multiple reflections in the MCSF films is successfully established, which can further boost the EMI shielding performance.…”
Section: Emi Mechanisms Of the Ti 3 C 2 T X Mxene/mwcnts/srfe 12 O 19...mentioning
confidence: 99%
“…The continuous domain walls and magnetic moments at the interface of two phases (marked areas C and D) depict the strong magnetic exchange coupling. [32,33] Figure 2a shows the high-angle annular dark-field HAADF-STEM image obtained along the [101] axis of ThMn 12 -type grain from the annealed Sm 0.75 Y 0.25 (Fe 0.8 Co 0.2 ) 11.25 Ti 0.75 alloy. The yellow-dashed square in Figure 2a is a close-up of the unit cell viewed along the [101] zone axis, which can be compared with the simulated unit cell with Sm(2a) in yellow, Fe(8f) in black, Fe(8i) in white, and Fe(8j) in gray.…”
Section: Resultsmentioning
confidence: 99%
“…The continuous domain walls and magnetic moments at the interface of two phases (marked areas C and D) depict the strong magnetic exchange coupling. [ 32,33 ]…”
Section: Resultsmentioning
confidence: 99%